Determining the effect of urbanization on bees and assessing land-sharing and land-sparing as conservation strategies - Brancher, Karla Palmieri Tavares (2022)
Urbanization is one of the most intense forms of landscape change and is likely to become more pronounced in the coming years, causing further damage to biodiversity. Studies have shown that bees are influenced by urbanization, due to the reduction of natural vegetation and the high proportion of impervious areas that replace the floral and nesting resources necessary for their survival. However, this knowledge is still limited, since most studies were carried out in large metropolises, where urbanization is notoriously more intense. In addition, the tropical region is underrepresented. Therefore, the main objective of this study was to evaluate the effects of urbanization on the bee community in medium-sized cities in Brazil. The present study was divided into three chapters. In the first chapter, we evaluated bee richness and abundance, their respective functional groups, and community composition along an urbanization gradient and concerning the plant community. Total bee richness decreased with increasing impervious cover and increased with landscape heterogeneity, which also had a positive effect on the richness of aboveground-nesting bees and generalist bees. The abundance of solitary bees and belowground-nesting bees were positively influenced by the increase in grass cover. The total number of native and exotic plants collected positively influenced the total abundance of bees, as well as the abundances of highly eusocial bees, which nest above- and belowground, and generalists. The number of native plants positively influenced the total richness and abundance of specialist bees. In the second chapter, we evaluated the effects of three forms of urban development on the bee community: land-sparing, land-sharing, and land fully occupied. We demonstrated a benefit of the land-sharing model, mainly concerning the land fully occupied model, as it presented greater species richness, genera richness, and a number of unique species. In the third and final chapter, we assess how the structure of interaction networks changes along an urbanization gradient. We also evaluated the importance of plant species and botanical families, to identify which ones attract more bees in urban environments. We found an increase in network connectance and interaction evenness with increasing urbanization, probably due to the loss of bee species. Some plant species and botanical families attracted more bee species, among them Asteraceae, Fabaceae, Bignoniaceae, Convolvulaceae, Malvaceae, Melastomataceae, and Lythraceae. We conclude that even in smaller cities with lower urbanization intensities, the bee communities were influenced by urbanization at the local and landscape scales. In addition, we present one of the few studies that have evaluated the effects of urban development models on biodiversity. Our study provides important results for understanding the effect of urbanization on bee communities in medium-sized cities, contributing to knowledge about the protection of native biodiversity in the face of rapid urban growth.